The Transcriptomic Profile of Monocytes from Patients With Sjögren’s Syndrome Is Associated With Inflammatory Parameters and Is Mimicked by Circulating Mediators - Lopes, Ana P.; Bekker, Cornelis P. J.; Hillen, Maarten R.; Blokland, Sofie L. M.; Hinrichs, Anneline C.; Pandit, Aridaman; Kruize, Aike A.; Radstake, Timothy R. D. J.; van Roon, Joel A. G. (Frontiers in Immunology, 2021)
Primary Sjögren’s syndrome (pSS) is a systemic autoimmune disease characterized by infiltration of the exocrine glands and prominent B cell hyperactivity. Considering the key role of monocytes in promoting B cell hyperactivity, we performed RNA-sequencing analysis of CD14+ monocytes from patients with pSS, non-Sjögren’s sicca (nSS), and healthy controls (HC). We demonstrated that the transcriptomic profile of pSS patients is enriched in intermediate and non-classical monocyte profiles, and confirmed the increased frequency of non-classical monocytes in pSS patients by flow-cytometry analysis. Weighted gene co-expression network analysis identified four molecular signatures in monocytes from pSS patients, functionally annotated for processes related with translation, IFN-signaling, and toll-like receptor signaling. Systemic and local inflammatory features significantly correlated with the expression of these signatures. Furthermore, genes highly associated with clinical features in pSS were identified as hub-genes for each signature. Unsupervised hierarchical cluster analysis of the hub-genes identified four clusters of nSS and pSS patients, each with distinct inflammatory and transcriptomic profiles. One cluster showed a significantly higher percentage of pSS patients with higher prevalence of anti-SSA autoantibodies, interferon-score, and erythrocyte sedimentation rate compared to the other clusters. Finally, we showed that the identified transcriptomic differences in pSS monocytes were induced in monocytes of healthy controls by exposure to serum of pSS patients. Representative hub-genes of all four signatures were partially inhibited by interferon-α/β receptor blockade, indicating that the circulating inflammatory mediators, including type I interferons have a significant contribution to the altered transcriptional profile of pSS-monocytes. Our study suggests that targeting key circulating inflammatory mediators, such as type I interferons, could offer new insights into the important pathways and mechanisms driving pSS, and holds promise for halting immunopathology in Sjögren’s Syndrome.